2019
DOI: 10.1148/radiol.2019190485
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity Reactions to Iodinated Contrast Media: A Multicenter Study of 196 081 Patients

Abstract: Background: Multicenter studies may be required for establishing guidelines for safe usage of iodinated contrast media (ICM).Purpose: To identify the prevalence, patterns, risk factors, and preventive measures for ICM-related hypersensitivity reactions (HSRs). Materials and Methods:Between March 2017 and October 2017, a total of 196 081 patients who underwent ICM administration were enrolled from seven participating institutions. The occurrence of HSRs and baseline patient information were recorded. x 2 and St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
76
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 19 publications
9
76
3
3
Order By: Relevance
“…In this regard, risk identification and related stratification in candidates for CAG are still critical for prophylaxis of ICM-associated AU or other immediate HSRs. Our results confirmed that atopy inpatients with immediate HSRs to ICM in previous CAG, preexisting allergic rhinitis, bronchial asthma, and antibiotics allergy are predisposed to the onset of AU during CAG, which were almost consistent with the findings from previous studies grouping all allergic reactions together in prophylactic and non-prophylactic patients ( 12 , 18 ). Additionally, the present study found that decreased eGFR or inflammation with mildly elevated Hs-CRP and NLR were also risk factors for the occurrence of ICM-related AU, which has not been unmasked previously.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this regard, risk identification and related stratification in candidates for CAG are still critical for prophylaxis of ICM-associated AU or other immediate HSRs. Our results confirmed that atopy inpatients with immediate HSRs to ICM in previous CAG, preexisting allergic rhinitis, bronchial asthma, and antibiotics allergy are predisposed to the onset of AU during CAG, which were almost consistent with the findings from previous studies grouping all allergic reactions together in prophylactic and non-prophylactic patients ( 12 , 18 ). Additionally, the present study found that decreased eGFR or inflammation with mildly elevated Hs-CRP and NLR were also risk factors for the occurrence of ICM-related AU, which has not been unmasked previously.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of AU may be underreported as some self-limited AU might be unnoticed. Furthermore, we could not rule out the effect of other drugs consumed, especially heparin, on the incidence of AU during CAG, but related drug hypersensitivity could be negligible judging from the rate of HSRs during computed tomography procedures without application of these drugs ( 1 , 10 , 12 ). A scientifically proven explanation for the difference between limited and diffuse AU could not be provided.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, iodinated contrast media (ICM) has now emerged as one of the "new" drugs for which skin testing has become increasingly used, likely for several reasons. These include the increasing incidence of solid organ cancers in the region, in particular with our ageing population; the increasing need for repeated computed tomography scans/magnetic resonance imaging for follow-up and surveillance increasing the risk of developing DHR, and because of the extensive work done by our colleagues in Korea on ICM hypersensitivity [61].…”
Section: Discussionmentioning
confidence: 99%
“…However, CT involves radiation, and various neoplasms may have similar imaging features on CT ( 3 , 4 ). Furthermore, contrast-enhanced CT may cause contrast-induced adverse reactions, though it is generally considered safe, with an overall prevalence of adverse reactions around 0.7%, among which most of the events (more than 80%) are mild ( 5 ). Ultrasound is a cheap and effective tool for delineating cystic versus solid tumors, tumor borders, and cervical lymph nodes; however, it poorly visualizes the deep lobe and is dependent on operator expertise.…”
Section: Introductionmentioning
confidence: 99%